Socioeconomic multi-domain health inequalities in Dutch primary school children. (9th April 2018) - Vermeiren, Angelique P; Willeboordse, Maartje; Oosterhoff, Marije; Bartelink, Nina; Muris, Peter; Bosma, Hans
Abstract: Background: This study assesses socio-economic health inequalities (SEHI) over primary school-age (4- to 12-years old) across 13 outcomes (i.e. body-mass index [BMI], handgrip strength, cardiovascular fitness, current physical conditions, moderate to vigorous physical activity, sleep duration, daily fruit and vegetable consumption, daily breakfast, exposure to smoking, mental strengths and difficulties, self-efficacy, school absenteeism and learning disabilities), covering four health domains (i.e. physical health, health behaviour, mental health and academic health). Methods: Multilevel mixed effect (linear and logistic) regression analyses were applied to cross-sectional data of a Dutch quasi-experimental study that included 1403 pupils from nine primary schools. Socioeconomic background (high-middle-low) was indicated by maternal education ( n = 976) and parental material deprivation ( n = 784). Results: Pupils with higher educated mothers had lower BMIs, higher handgrip strength and higher cardiovascular fitness; their parents reported more daily fruit and vegetable consumption, daily breakfast and less exposure to smoking. Furthermore these pupils showed less mental difficulties and less school absenteeism compared with pupils whose mothers had a lower education level. When using parental material deprivation as socio-economic indicator, similar results were found for BMI, cardiovascular fitness, sleep duration, exposure to smoking and mental strengths and difficulties. Socio-economic differences in handgrip strength, cardiovascular fitness and sleep duration were larger in older than in younger pupils. Conclusions: Childhood SEHI are clearly found across multiple domains, and some are larger in older than in younger pupils. Interventions aiming to tackle SEHI may therefore need a comprehensive and perhaps more fundamental approach.